2021
DOI: 10.1186/s13071-021-04921-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Sarcocystis halieti in the muscles of two species of birds of prey from Spain

Abstract: Background Members of the genus Sarcocystis are protozoan parasites characterized by a prey–predator two-host life-cycle. Sarcocysts are formed in the muscles or central nervous system of the intermediate host (IH), while sporocysts develop in the small intestine of the definitive host (DH). Various birds of prey have been confirmed to be DH for Sarcocystis spp. Three Sarcocystis species, S. wobeseri, S. halieti and S. falcatula, have been identified in the muscles of birds of prey, of which th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In Spain, after examining a congeneric bird species, the black kite M . migrans , Prakas et al (2021) found muscular sarcocysts in this host and considered it as S . halieti , which formed a sister branch to other sequences of the same species.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In Spain, after examining a congeneric bird species, the black kite M . migrans , Prakas et al (2021) found muscular sarcocysts in this host and considered it as S . halieti , which formed a sister branch to other sequences of the same species.…”
Section: Discussionmentioning
confidence: 81%
“…halieti ( Mayr et al, 2016 ). More recently, the herring gull from Lithuania ( Prakas et al, 2020 ), the black kite and the western marsh harrier from Spain ( Prakas et al, 2021 ), and the little owl ( Athene noctua [Scopoli, 1769]) from Germany ( Maier-Sam et al, 2021 ), were all reported as intermediate hosts of S . halieti ; whereas oocysts were found in the intestinal mucosa of corvid birds from Lithuania ( Juozaityté-Ngugu et al, 2021 ), as well as in the Cooper's hawk ( Accipitter cooperi [Bonaparte, 1828], the red-shouldered hawk ( Buteo lineatus [Gmelin, 1788]) and the red-tailed hawk ( B .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…kutkienae form sarcocysts in muscles of corvids, while S . halieti is multi-host adapted, employing birds of several different orders as IH [ 45 , 46 ]. Birds of prey are identified DH of S .…”
Section: Discussionmentioning
confidence: 99%